Etika Publik bagi Kepemimpinan Pemerintah Daerah - Sumarto, Rumsari Hadi (Publisia: Jurnal Ilmu Administrasi Publik, 2017)
Ethics has always been a part of human life in which ethics as a guide to judge the good of an action. Ethics is actually very close to one’s life including public leaders. If the public leader always presents ethics in every action, then the public leader will be able to minimize actions that conflict with ethical values, including in cases of corruption. Ethical values that should be used as guidance for public leaders, especially the head of the region seems to lose its meaning when the head of the region committed ethical violations such as corruption cases. Therefore, it is important to understand that public ethics can fortify regional heads to keep acting in accordance with prevailing norms and not to deny public ethics. Public ethics that always be the basis of behavior of the head of the region will bring to the head of the region that is able to represent itself as a person who has personal integrity and can be an example for the bureaucratic apparatus and society in a region. DOI:Â https://doi.org/10.26905/pjiap.v2i2.1929